Theoretical foundations of Florence Nightingale on hand hygiene. Notes for a reflection in times of COVID-19 - Zenia Tamara Sánchez García; Yuliet Mora Pérez; Leoana Lázara González Ricardo; Julia Maricela Torres Esperón; José Noel Marrero Rodríguez; Jacobo Cambill Martín (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2021)
A review is presented, from the paradigm of Florencia Nightingale, on her theoretical vision about hand hygiene. The main theoretical aspects expressed by her and her relationship with hand hygiene are analyzed, in addition to exposing, through the analysis of her theoretical contributions, her contribution to the development of nursing not only in Cuba but in the world, showing the importance that has this practice to combat a number of infectious diseases and very specifically COVID-19, since one of the most important measures to break its chain of transmission is precisely hand hygiene.